Evaluasi Pengajian Kitab Kuning Menggunakan Model Cipp di Pondok Pesantren Alfakhriyah Multidimensi Makassar - Huseng, Andi Maggalatung; Auliyauddin, Shoif; Rasyid, Muhammad Nur Akbar; N, Nursalam (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The study of the yellow book is one of the most important traditions in the world of boarding schools that have always played a major role in shaping the character and knowledge of students. However, amid the rapidly changing times, a new challenge emerges: how to make the study of the Yellow Book remain relevant to the needs of today’s students living in an all-digital world and full of social dynamics. This study aims to evaluate the implementation of yellow book study in Makassar Multidimensional Alfakhriyah Boarding School using the CIPP (Context, Input, Process, Product) evaluation model. The research was conducted with a contextual qualitative approach through observation, interviews, and documentation. The evaluation results show that contextually, the book study program is still very important and relevant. In terms of inputs, the quality of teaching is excellent, yet it is still constrained by facilities and minimal utilization of technology. The learning process begins to shift from one-way methods to a more interactive and dialogic two-way approach. Meanwhile, the learning results showed that students were quite mastering the content of the book textually, but still needed reinforcement in critical thinking and the ability to communicate knowledge to the public. Based on these findings, it is recommended that boarding schools begin to pursue more contextualized curriculum innovations, opening spaces for exploration in learning, as well as equipping students with skills that support their role amid modern society.